2015
DOI: 10.2112/si73-093.1
|View full text |Cite
|
Sign up to set email alerts
|

Study on Load-bearing Characteristics of Different Types of Pile Group Foundations for an Offshore Wind Turbine

Abstract: Lang, R.; Liu, R.; Lian, J., and Ding, H., 2015. Study on load-bearing characteristics of different types of pile group foundations for an offshore wind turbine.Elevated pile-cap foundation is one of the most popular foundation types for offshore wind turbines. Form selection and design are the keys in the construction of offshore wind farms. Because offshore wind turbines are high-rise structures, a reasonable and applicable foundation can ensure the normal operation of wind turbines. Meanwhile, it can decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Wang et al [13] evaluated the ground, pile foundation, and overall bridge seismic response. Lang et al [14] investigated the dynamic behavior of a reinforced-concrete (RC) elevated cap-pile foundation during (and prior to) soil liquefaction. Wang et al [15] showed that a displacement ductility capacity of 3.5 is observed for the elevated pile cap foundation.…”
Section: Related Research On High Pile Cap and Low-pile Capmentioning
confidence: 99%
“…Wang et al [13] evaluated the ground, pile foundation, and overall bridge seismic response. Lang et al [14] investigated the dynamic behavior of a reinforced-concrete (RC) elevated cap-pile foundation during (and prior to) soil liquefaction. Wang et al [15] showed that a displacement ductility capacity of 3.5 is observed for the elevated pile cap foundation.…”
Section: Related Research On High Pile Cap and Low-pile Capmentioning
confidence: 99%
“…Weyers [25] studied the service life of reinforced concrete in a chlorine-containing environment by numerical simulation and established a corresponding prediction model. Lang et al [26,27] studied the bearing characteristics of four different types of marine bridge pile foundations by a numerical simulation model. Feng et al [28] studied the bearing characteristics of bridge pile foundations under the condition of liquefaction of foundation soil by improving a numerical simulation calculation method.…”
Section: Introductionmentioning
confidence: 99%